Mapeamento da zona costeira protegida por arenitos de praia (Beachrocks) em Nísia Floresta - RN - Ferreira Júnior, Antonio Vicente (2005)
The goal of this work comprises the detailed mapping of the coastal zone of the south coast of the State of Rio Grande do Norte. The emphasis of the study is the units of beachrocks and the features of the physical environment associated. The mapping of the beachrocks and of the adjacent coastal features is justified, among other aspects, by the fact that the beachrocks constitute an important protection agent against the sea erosion. By one side, they dissipate the energy of the sea waves and make possible the imprisonment of sediments in the foreshore. The beachrocks in the studied area are constituted of discontinuous strips, parallel to the coast line presenting emerged in some places, even in the highest tides, entirely submerged or partially buried by coastal sediments. These sandstones compose the landscape of big part of the coast and they are responsible for the partial dissipation of the energy of the waves on the studied coast. The methodology used in this work consisted of different techniques were used, as the use of aerial pictures of small format (FAPEFs), acquisition of data of system of global positioning (GPS) and later elaboration of thematic maps and of digital models of soil (MDTs). The results obtained in the mapping of the use and occupation of the soil, demonstrate the existence of strong human pressure in the coastal area (built lots and no built), occupying about 54,74% of built areas. This problem has been taking to degradation risks due to the inconsequent expansion of divisions into lots and tourist enterprises. The MDT came as an excellent resource, as visual as functional, being possible to visualize several angles and to act in three dimensions the relief of the area in study, as well as to identify the present features in the coastal area. By the importance of the bodies of beachrocks as a protection agent against the coastal erosion, faces were delimited in the sandstones based in geometric criteria, classifying them in, central face, outside face, inside face, break and undermiming. These last two associates to the erosion and washout in the base of these bodies. Field data indicate clearly that the most important process in the fracturing of the bodies is associated with mechanisms related to the gravity, being the joints formed by processes of gravitational sliding. Finally, the mapping of the coastal zone starting from aerial pictures of small format it made possible the identification of the elements that compose the beach strip, for accomplishing with larger detailed level and by presenting a better monitoring of the dynamics of the coastal zone